Female Headship and Poverty in the Arab Region: Analysis of Trends and Dynamics Based on a New Typology - Shireen AlAzzawi; Hai-Anh Dang; Vladimir Hlasny; Kseniya Abanokova; Jere R. Behrman (Institute of Labor Economics (IZA), 2023)
Various challenges are thought to render female-headed households (FHHs) vulnerable to poverty in the Arab region. Yet, previous studies have mixed results and despite the availability of cross-sectional data, the absence of household panel survey data hinders analysis of poverty dynamics. We address these challenges by proposing a novel typology of FHHs and analyze synthetic panels that we constructed from 20 rounds of repeated cross-sectional surveys spanning the past two decades from Egypt, Iraq, Jordan, Mauritania, Palestine, and Tunisia. We find that the definition of FHHs matters for measuring poverty levels and dynamics. Most types of FHHs are less poor, but FHHs with a major share of female adults are generally poorer. FHHs are more likely to escape poverty than households on average, but FHHs without children are most likely to do so. While more children are generally associated with more poverty for FHHs, there is heterogeneity across countries is addition to heterogeneity across FHH measures. Our findings provide useful inputs for social protection and employment programs aiming at reducing gender inequalities and poverty in the Arab region.
Keywords: I3; J16; N35; O1; 330; poverty; feminization; female-headedness typology; synthetic panels; Arab region; household surveys